Is there evidence for a close connection between side of intravesical tumor location and ipsilateral lymphatic spread in lymph node-positive bladder cancer patients at radical cystectomy?: results of the PROMETRICS 2011 database - May, Matthias; Protzel, Chris; Nuhn, Philipp; Hadaschik, Boris (International urology and nephrology, 2017)
PurposeTo evaluate the possible association between bladder tumor location and the laterality of positive lymph nodes (LN) in a prospectively collected multi-institutional radical cystectomy (RC) series.Methods The study population included 148 node-positive bladder cancer (BC) patients undergoing RC and pelvic lymph node dissection in 2011 without neoadjuvant chemotherapy and without distant metastasis. Tumor location was classified as right, left or bilateral and compared to the laterality of positive pelvic LN. A logistic regression model was used to identify predictors of ipsilaterality of lymphatic spread. Using multivariate Cox regression analyses (median follow-up: 25 months), the effect of the laterality of positive LN on cancer-specific mortality (CSM) was estimated.ResultsOverall, median 18.5 LN [interquartile range (IQR), 11-27] were removed and 3 LN (IQR 1-5) were positive. There was concordance of tumor location and laterality of positive LN in 82% [95% confidence interval (CI), 76-89]. Patients with unilateral tumors (n = 78) harbored exclusively ipsilateral positive LN in 67% (95% CI 56-77). No criteria were found to predict ipsilateral positive LN in patients with unilateral tumors. CSM after 3 years in patients with ipsilateral, contralateral, and bilateral LN metastasis was 41, 67, and 100%, respectively (p = 0.042). However, no significant effect of the laterality of positive pelvic LN on CSM could be confirmed in multivariate analyses.ConclusionsOur prospective cohort showed a concordance of tumor location and laterality of LN metastasis in BC at RC without any predictive criteria and without any influence on CSM. It is debatable, whether these findings may contribute to a more individualized patient management.